Effect of Factors on the Hydrolysis of Red Rice (Oryza Punctate) by Spezyme Alpha - Dang, Tien Thanh; Duong, Thi Du; Chu, Ky Son; Vu, Thu Trang (Old Journal, 2019)
This study investigates several factors affecting the hydrolysis of red rice by Spezyme Alpha (α-amylase) for red rice-based drink. Effect of factors such as dry matter concentration, hydrolysis temperature, enzyme concentration on the hydrolysis of red rice was investigated in this study with the aim of finding suitable condition to producing red rice-based drink. The reducing sugar content, starch content, DE (Dextrose Equivalent) index and hydrolysis yield were examined. The results indicated that the suitable hydrolyzing conditions of rice were 80g/l in dry matter; Hydrolysis temperature: 83°C; 60 min; Enzyme concentrations: 0.048%w/v. The liquefied yield achieved 73.02%; DE index: 7.28%.